EXPLORING THE CONCEPT OF HAPPINESS: A COMPARATIVE STUDY OF ENGLISH AND UZBEK EXPRESSIONS - Ashurokhunova Dildora Toxir qizi , (TADQIQOTLAR.UZ, 2024)
Abstract: Happiness is a universal concept that is often expressed through language. This study aims to explore the expression of the concept of happiness in English and its translation into Uzbek. By comparing the linguistic and cultural aspects of these expressions, we can gain a deeper understanding of how happiness is perceived and communicated in these languages.